Elementary school students’ knowledge of gadget and internet use after receiving a psychoeducation program - Afiatin, Tina; Ampuni, Sutarimah; Rachmanie, Aisha Sekar Lazuardini; Muhtadini, Rahmita Laily; Firdaus, Muhammad Iqbal Fakhrul; Hanifah, Salma Nur; Aprila, Anggia Atin; Kusumawati, Yutia Cesarinda; Permatasari, Alfia Rahma (Jurnal Ilmiah Psikologi Terapan, 2025)
The increasing use of technology, especially gadgets and the internet, among elementary students brings both benefits and risks, highlighting the importance of wise and safe usage. The psychoeducation program “Cerdas Menggunakan Gadget dan Internet untuk Anak” (Smart Use of Gadgets and the Internet for Children) explored students’ understanding before and after participation. This qualitative study used open-ended questions and thematic content analysis. Participants were 83 students aged 10–11 years from an elementary school in Yogyakarta. Before the program, students’ knowledge was limited, shown by vague responses. Afterward, their answers were more detailed and specific, including examples of proper gadget and internet use. However, most still viewed technology mainly as a source of entertainment and games. These findings highlight the need for continued psychoeducation to strengthen children’s digital literacy and safety. A key limitation is the small sample size and the focus on cognitive understanding without assessing behavioral outcomes.